Inseparable : the original Siamese twins and their rendezvous with American history - Huang, Yunte (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2018)
A portrait of nineteenth-century conjoined twins Chang and Eng Bunker describes their rise from savvy side-show celebrities to wealthy Southern gentry and discusses how their experiences reflected America's historical penchant for objectifying differences.